Flexing Sebagai Komunikasi Simbolik Pada Judul Konten “Ah Official Youtube Channel” - Sri Rahayu (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2022)
This research aims to publish the flexing culture in the 5.0 era that occurred in the midst of Indonesian society. This research study uses a qualitative research methodology with visual analysis. The approach of this research is Spredly's two-stage symbol analysis, namely signifier (expression/signifier) ​​and signified (content/signifier). While the primary data used in this study is the wording in the title sentence of the AH Official YouTube Channel content, where incidental data retrieval was carried out on June 1-20 July. The theory used in this research is the theory of denotation and connotation by Barthes. The focus of this study is on flexing culture as a symbolic communication contained in the object of research, along with observations. The results of this study are that the AH Official YouTube Channel as a verified account that has the largest number of followers in Southeast Asia takes actions to stretch its YouTube content, including flexing on transactions to fulfill personal needs, flexing against individual emotional actions, flexing over face values, flex to offer something.